THE STEM BORER INFESTATION ON RICE CULTIVARS AT THREE PLANTING TIMES - Hendarsih Suharto; N. Usyati (Indonesian Journal of Agricultural Science, 2005)
Stem borer is the second important rice pest after rats in Indonesia. A field trial was conducted in Karawang, West Java in dry season of 2003 to study the effect of planting time on the stem borer infestation on seven rice cultivars. The rice cultivars tested were Fatmawati (new plant type cultivar), Gilirang (semi-new plant type cultivar), Maro and Intani 3 (hybrid rice cultivars), and IR72, Cilosari and IR62 (inbreed rice cultivars). The three planting times (PT) were: (1) the early PT, 14 days before farmer’s PT, (2) the common PT, simultaneously with farmer’s PT, and (3) the late PT, 14 days after farmer’s PT. The trial was arranged in a split plot design with four replications. Planting time is the main plot and rice cultivar is the subplot. Fourteen-day old rice seedlings were transplanted at 25 cm x 25 cm planting distance in a 5 m x 6 m plot size. Species and fluctuation of rice stem borer were determined by using water traps containing four synthetic sex pheromone lures of rice stem borer species as attractant. Results showed that the dominant species of stem borer was yellow stem borer (Scirpophaga incertulas Wlk.). Degree of stem borer infestation depended upon the planting time. Stem borer infestation at the first planting time was higher (average 37.90%) compared to those found at the second and third planting time, i.e. 0.65% and 0.54%, respectively. Rice yields of Fatmawati, Gilirang, Maro, Intani-3, and Cilosari cultivars correlated with the degree of stem borer infestation, but did not correlate with planting time. Cilosari cultivar showed the most tolerant under heavily stem borer infestation. The present study implies that adjustment of planting time is the most feasible effort to reduce stem borer infestation because none of the seven rice cultivars tested were able to minimize damage under heavily infestation of yellow stem borer.